The gas content distribution of coal reservoir at the Changzhi block, south-central Qinshui Basin, North China: Influences of geologic structure and hydrogeology. Issue 1 (January 2019) - Du, Zhigang; Zhang, Xiaodong; Huang, Qiang; Zhang, Shuo; Wang, Chenlin
Coalbed methane is now large-scalely explorated and exploitated in the world. The Changzhi coalbed methane block, south-central Qinshui Basin, is a new resource target zone for coalbed methane exploration and exploitation in China. However, the gas content distribution of this block and its influential factors have not yet studied. Based on the recent coalbed methane exploration and exploitation activities, the gas content distribution of coal reservoir in this block was studied. The results show that the gas content hold by the coal reservoir is 7.0 − 21.7 m 3 /t, which was determined by a combining control effect from geologic structure and hydrogeology. The Changzhi coalbed methane block has experienced multiple-stages geologic structure evolution, especially a tectonic-thermal event during the middle Yanshanian Orogeny improved the coal to the current R o, max 1.9 − 2.7% and meanwhile the coalbed methane was greatly generated. Subsequently, the widespreadly developed normal fault structures during the Himalayan Orogeny accelerated the coalbed methane escape through the "gas escape windows", particularly where the location within the distance of about 1300 m to the "gas escape window" the gas content decreases significantly. Moreover, due to the action of the later Himalayan Orogeny, the slope areas of most Yanshanian fold structures were structurally cross-cut by the Himalayan normal faults, and thus an "open" syncline folds were formed. The coal reservoir was depressurized surrounding this "open" syncline structure and consequently the hydrodynamic losing effect has resulted in a comparatively lower gas content therein. By the control of geologic structure and hydrogeology, this block can be generally, compartmentalized into three hydrodynamic systems including the western groundwater stagnation region, the middle runoff region, and the north-eastern recharge region, where the hydrodynamic sealing effect at the groundwater stagnation region has made a comparatively higher gas content for the coal reservoir, but the hydrodynamic losing effect at the recharge region and runoff region has made a comparatively lower gas content of the coal reservoir.